PERSONAL SELLING SEBAGAI KOMUNIKASI PEMASARAN PRODUK INDIHOME PT. TELKOM PALU - Faisal; Zainuddin, Sumarni; Alfiyaty, Rizqy (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2019)
This study aims to determine the form of Personal Selling by PT. Telkom as well as knowing the Personal Selling process carried out by PT. Telkom Palu. The type of research used is descriptive qualitative type. The basis of research in this study is a case study, data collection techniques used are observation and in-depth interviews. The data analysis technique used in this research is the data analysis technique of Miles and Huberman's interactive analysis model, namely data reduction, data presentation, conclusion drawing and verification. The results showed that the form of Personal Selling that occurred at PT. Telkom Palu, namely, (1) retail sales, sales serving prospective customers who come to the company, (2) field sales, sales selling outside the company, and (3) executive sales, PT. Telkom Palu involves agency leaders in product marketing. The Personal Selling process that occurs are, (1) looking for potential customers, sales canvassing related to customer references, (2) preliminary approach, sales start a relationship with the initial steps, namely several personal visits, telephone and sms, (3) approach, sales look attractive and be polite and attentive to potential customers, (4) presentation and demonstration, sales bring supporting tools that support smooth activities, (5) overcome objections, sales when meeting potential customers, by making sales, and listening to all complaints related to IndiHome product problems, (6) closing sales, sales recognizing signs given by customers in the form of statements or comments, and (7) following up, sales ensuring customer satisfaction and repeat purchases. This has been done by PT. Telkom Palu in order to attract interest and increase sales of telecommunication service products.